A 4E feasibility analysis of an on-site, ammonia sourced, hydrogen refueling station. (20th August 2022) - Lim, Dongjun; Lee, Aejin; Kim, Ayeon; Haider, Junaid; Mikulčić, Hrvoje; Brigljević, Boris; Lim, Hankwon
Abstract: Since hydrogen (H2 ) demand in the transportation field has increased as a result of efforts to reduce carbon emissions, the number of H2 refueling stations has been increasing as well. However, the transportation of H2 itself requires a lot of energy due to the low volumetric density of H2 necessitating energy-intensive processes of compression or liquefaction. In this context, ammonia (NH3 ) has been emerging as an efficient H2 carrier with several beneficial characteristics such as a large weight fraction of H2 (17.65%), and liquefaction at ambient temperature and moderate pressures which allows for the utilization of existing fossil fuel infrastructure. Thus, NH3 can be utilized as an H2 transport medium as well as a raw material for remote H2 refueling stations. In this study, a comparative 4E (energy, exergy, economic, and environmental) analysis of an H2 refueling station supplied from an on-site NH3 reforming using a packed bed reactor (PBR) and a membrane reactor (MR) is performed. Due to the higher H2 recovery in the MR, a greater H2 production rate is observed resulting in lower H2 production cost. Compared to the PBR, energy and exergy efficiency in the MR-based process are improved by 3.6%p and 2.7%p reaching 82.7% and 78.7%, respectively, and greenhouse gas emissions are reduced by ∼17% from 5.4 to 4.5 kgCO2 -eq kgH2 −1 . The break-even price of H2 in the MR-based process at present is 8.1–9.2 USD kgH2 −1 (at scale of 900 kgH2 d −1 ) and the break-even points with the H2 selling price of 12.5 USD kg H2 −1 are 7.8–8.9 y whereas the corresponding values are 9.4–10.5 USD kgH2 −1 and 10.2–12.3 y in the process using the PBR. At an H2 selling price of 7.5 USD kgH2 −1, most cases (90.6%) of the net present value in the MR-based process were positive in 2040 indicating an economically feasible process, while cases with lower H2 selling price (2.5 and 5.0 USD kgH2 −1 ) were not deemed profitable under current technological level. Highlights: Process design and simulation of an ammonia-based, H2 refueling station. The choice of a packed bed reactor or a membrane reactor is evaluated. 4E (Energy, Exergy, Economic, and Environmental) analysis is performed. The membrane reactor-based process can be feasible in 2040 for 7.5 USD kgH2 −1 . CO2 emissions can be reduced by 58–64% compared to conventional H2 production.